Flexible, Printable Soft‐X‐Ray Detectors Based on All‐Inorganic Perovskite Quantum Dots. Issue 30 (6th June 2019) - Liu, Jingying; Shabbir, Babar; Wang, Chujie; Wan, Tao; Ou, Qingdong; Yu, Pei; Tadich, Anton; Jiao, Xuechen; Chu, Dewei; Qi, Dongchen; Li, Dabing; Kan, Ruifeng; et al.
Abstract: Metal halide perovskites represent a family of the most promising materials for fascinating photovoltaic and photodetector applications due to their unique optoelectronic properties and much needed simple and low‐cost fabrication process. The high atomic number ( Z ) of their constituents and significantly higher carrier mobility also make perovskite semiconductors suitable for the detection of ionizing radiation. By taking advantage of that, the direct detection of soft‐X‐ray‐induced photocurrent is demonstrated in both rigid and flexible detectors based on all‐inorganic halide perovskite quantum dots (QDs) synthesized via a solution process. Utilizing a synchrotron soft‐X‐ray beamline, high sensitivities of up to 1450 µC Gyair −1 cm −2 are achieved under an X‐ray dose rate of 0.0172 mGyair s −1 with only 0.1 V bias voltage, which is about 70‐fold more sensitive than conventional α‐Se devices. Furthermore, the perovskite film is printed homogeneously on various substrates by the inexpensive inkjet printing method to demonstrate large‐scale fabrication of arrays of multichannel detectors. These results suggest that the perovskite QDs are ideal candidates for the detection of soft X‐rays and for large‐area flat or flexible panels with tremendous application potential in multidimensional and different architectures imaging technologies. Abstract : The direct detection of soft‐X‐ray‐induced photocurrent in both rigid and flexible detectors based on all‐inorganic halide perovskite quantum dots is reported. Utilizing inexpensive inkjet printing, perovskite film is printed homogeneously on various substrates to demonstrate large‐scale fabrication. These types of detectors are ideal candidates for applications in the detection of soft/hard X‐rays and for large‐area flat/flexible imaging technologies.